Designing framework of a segmented rubber tracked vehicle for Sepang peat terrain in Malaysia - Rahman, Mohammed Ataur; Yahya, Azmi; Bardaie, Mohd. Zohadie; Wan Ismail, Wan Ishak (IIUM Press, 2005)

(untitled)
The focus of this paper to present the designing framework of an off-road special segmented rubber tracked vehicle that may be required to run on low bearing capacity peat terrain. To complete this study: firstly, mechanical properties of peat terrain were first determined by using different type of apparatus. Direct shear test was performed using a Wykeham Farrance 25402 shear box apparatus to determine the internal friction angle, cohesiveness and shear deformation modulus of the peat sample. Load-sinkage test was performed using a specially made bearing capacity apparatus to determine the stiffness values of surface mat and underlying peat. Secondly, substantiate the validity of the mathematical model and finally design parameters of the special segmented rubber tracked vehicle were optimized by simulation.